Naltrexone and Its Noroxymorphone Minor Metabolite – A Case Report. Issue 2 (14th March 2020) - Stanciu, Cornel N.; Gnanasegaram, Samantha
ABSTRACT: As part of substance use maintenance programs, individuals are monitored for sobriety through urine drug screens. A positive screen, and its confirmation and interpretation, can have devastating consequences, sometimes even leading to termination from the program and relapse. Naltrexone metabolism involves several steps and metabolites – one minor metabolite with very little mention in medical literature being noroxymorphone. This is also the final intermediate in the metabolic pathway of oxycodone; hence, detection is naturally presumed by clinicians to be attributed to oxycodone use. Through this case report, we alert clinicians that, depending on individual pharmacogenomics, it is possible to obtain a positive confirmation of this component alone (without any oxycodone pathway intermediates) with naltrexone administration.